Hanuman Dance: A cultural identity of Newar in Baglung - Sharma, Shyam (Pragnya Sarathi प्रज्ञा-सारथि, 2024)
The performative dimension of a cultural dance encompasses various elements such as body movements, gestures, facial expressions, costumes, music, and storytelling, all of which come together to convey meaning, emotion, and cultural identity. It’s not just about the physical movements but also about the expression of values, beliefs, and traditions within a community and society. This research analyses the performative dimension of Hanuman dance as a cultural performance among Newar community of Baglung. This dance, in Baglung, has been promoted, preserved and performed by Newar people. They have long-term impact of their own traditional rituals and they have not avoided the culture especially based on their caste and ethnicity. They perform various kinds of dances and dance dramas which are an important part of their cultural and ritual practices. These performances are the key elements in introducing the culture of the community and they are remaining as the chief sources of their cultural heritage. Among various kinds of cultural folk performances that are traditionally adopted in the community Hanuman dance, Nagnagini dance, Voteshelo dance, Jogi dance, Lakhe dance and Ropain dance are widely popular in Dhawalagiri region. Every ritual performance does have its own cultural aesthetic and this aesthetic can be exposed through the means of performance. Cultural dance as performance is a display of social or cultural activities and the representation of community activity. Thus, this paper attempts to analyze Hanuman Dance as a cultural performance as cultural performances are vibrant showcases of tradition, rhythm, and religion, often reflecting the rich heritage and customs of a particular community or region. From the graceful movements of ballet to the energetic steps of Hanuman dance, each performance offers a unique glimpse into the cultural identity of it’s’ performers. The wholesale analysis of the dance performance will be carried out in the light of Richard Schechner’s concept of “Ritual and Performance”, “Fundamental of Performance Studies”, Victor Turner’s “Liminality and Communitas”, “Liminal to Liminoid, in Play, Flow and Ritual”, Abhi Subedi’s “Nepali Theatre as I See It”, and M. Certeau’s “Walking in the City” etc. The tentative conclusion at which the analysis will arrive is that The Hanuman Dance not only entertains the audiences and participants but also preserves and promotes cultural identity and social harmony.